2020
DOI: 10.1097/aln.0000000000003655
|View full text |Cite|
|
Sign up to set email alerts
|

Appropriate Clinical Use of Lactate Measurements

Abstract: Elevated lactate can result from many pathophysiologic processes. Understanding the mechanism of lactate production, metabolism, and the basics of lactic acidosis will enable the appropriate use of laboratory tests and interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 64 publications
(57 reference statements)
2
22
0
2
Order By: Relevance
“…Serum lactate has several limitations such as being elevated in several aerobic conditions (liver impairment, infections, and convulsions); and having slow dynamics. 13 Hernandez et al had found that 50% of the survivors of septic shock had persistently elevated lactate 24 h after resuscitation. 14 Thus, the use of a combined index was hypothesized to provide a more comprehensive marker than the use of either marker alone.…”
Section: Discussionmentioning
confidence: 99%
“…Serum lactate has several limitations such as being elevated in several aerobic conditions (liver impairment, infections, and convulsions); and having slow dynamics. 13 Hernandez et al had found that 50% of the survivors of septic shock had persistently elevated lactate 24 h after resuscitation. 14 Thus, the use of a combined index was hypothesized to provide a more comprehensive marker than the use of either marker alone.…”
Section: Discussionmentioning
confidence: 99%
“…The Third International Consensus Definitions for Sepsis and Septic Shock showed that elevated lactate levels are reflective of cellular dysfunction in sepsis [ 17 ]. Basic studies have shown that even if the body has no hypoxia, if mitochondrial function is damaged and the tissue cannot uptake oxygen normally, the lactic acid value will increase [ 18 ]. Obvious blood volume declines in the early period is characteristic of acute pancreatitis, hyperfusion causes organ dysfunction and reperfusion injury can exacerbate the severity of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Cerrahi sürenin uzun olması, doku hipoperfüzyonuna bağlı laktat artışı ve metabolik asidozun nedenlerindendir. Laktat artışı yetersiz doku perfüzyonunun önemli bir göstergesidir (16,27). Ongun ve ark.…”
Section: Metabolik Sorunlarunclassified
“…Perioperatif dönemde hiperglisemi de gözlenebilir. Hipergliseminin ateş, enfeksiyon, kan transfüzyonu, hipotermi gibi faktörlere bağlı olmadığının belirlenmesi gerekir (27). Bununla beraber hipergliseminin, mekanik ventilasyonda kalış süresi, yoğun bakımda ve hastanede kalış sürelerini uzatmadığı gösterilmiştir (28).…”
Section: Metabolik Sorunlarunclassified